2021
DOI: 10.1002/pbc.29336
|View full text |Cite
|
Sign up to set email alerts
|

Secondary impacts of constipation in acute lymphoblastic leukemia in U.S. children's hospitals

Abstract: Background Childrenwith acute lymphoblastic leukemia (ALL) suffer a litany of chemotherapy‐induced side effects. Constipation secondary to vinca alkaloids, psychological stressors, and opioid use are common issues for children newly diagnosed with leukemia. This study investigated the morbidity associated with constipation including infections, mucositis, and healthcare utilization in hospitalized children with ALL receiving induction chemotherapy. Methods We analyzed data from 48 children's hospitals in the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In a multicenter study, constipation was found to be prevalent in 34% of patients during induction, often requiring multiple medications for constipation management 17 . Constipation during induction increases a patient’s risk of having mucositis or perirectal issues 18 . With improved early education and intervention with a daily bowel regimen, we could decrease constipation in our patients with ALL, thereby reducing readmission and health care utilization for treatment-related constipation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a multicenter study, constipation was found to be prevalent in 34% of patients during induction, often requiring multiple medications for constipation management 17 . Constipation during induction increases a patient’s risk of having mucositis or perirectal issues 18 . With improved early education and intervention with a daily bowel regimen, we could decrease constipation in our patients with ALL, thereby reducing readmission and health care utilization for treatment-related constipation.…”
Section: Discussionmentioning
confidence: 98%
“…17 Constipation during induction increases a patient's risk of having mucositis or perirectal issues. 18 With improved early education and intervention with a daily bowel regimen, we could decrease constipation in our patients with ALL, thereby reducing readmission and health care utilization for treatment-related constipation.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned by Belsky et al, 1 it can be difficult to attribute the constipation solely to the medication being used. There are a variety of confounding factors that can arise during induction therapy that can also cause constipation-dietary changes due to hospital admission, lack of water intake due to fatigue, and lack of energy to exercise, to name a few.…”
Section: Comment On: Secondary Impacts Of Constipation In Acute Lymphoblastic Leukemia In Us Children's Hospitalsmentioning
confidence: 97%
“…We read with great interest, the article by Belsky et al 1 on the effects of constipation in pediatric oncology patients, particularly looking at children who had undergone induction therapy for acute lymphoblastic leukemia (ALL). As medical students who have recently had pediatric and oncology placements, we would like to share our thoughts on what we found to be a fascinating topic.…”
Section: Comment On: Secondary Impacts Of Constipation In Acute Lymphoblastic Leukemia In Us Children's Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation